2001
DOI: 10.1002/app.10002
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of linear low density polyethylene films by atomic force microscopy

Abstract: Atomic force microscopy has been used to investigate the morphology of hexene linear low density polyethylene (LLDPE) blown film in the undrawn and drawn states. The morphology of the undrawn film, which is biaxially oriented due to the nature of the extrusion process, is composed of crystallites, which consist of aggregates of lamellae. Elongation of the film caused these crystallites to undergo deformation, resulting in the gradual formation of a fibrillar structure in the draw direction. The transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Simply explained, the brighter yellow (light) regions represent stiffer structures at the surface and the darker regions represent softer structures. There are good reasons to believe that the stiffer regions have a higher crystalline content and that the softer regions are more amorphous 15, 16. The images were not easy to acquire for these samples because of residue particles (fiber residues) at the surfaces, and have to be interpreted with caution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simply explained, the brighter yellow (light) regions represent stiffer structures at the surface and the darker regions represent softer structures. There are good reasons to believe that the stiffer regions have a higher crystalline content and that the softer regions are more amorphous 15, 16. The images were not easy to acquire for these samples because of residue particles (fiber residues) at the surfaces, and have to be interpreted with caution.…”
Section: Resultsmentioning
confidence: 99%
“…There are good reasons to believe that the stiffer regions have a higher crystalline content and that the softer regions are more amorphous. 15,16 The images were not easy to acquire for these samples because of residue particles (fiber residues) at the surfaces, and have to be interpreted with caution. A corresponding AFM picture without disturbing artefacts for sample 2 was not achieved due to these reasons.…”
Section: Analyses Of the Hdpe Extrusion Coating Layermentioning
confidence: 99%
“…Classically, transformation from original spherulitic structure to fibrillar one, is a typical mechanism for cold drawing and yielding process in semi-crystalline polymers [16][17][18][19][20][21][22]. Peterlin in the 1960s proposed that drawing of polyethylene leads to permanent deformation of the lamellae causing the lamellae to tilt and slip, thereby rupturing into crystalline blocks.…”
Section: Crystalline Morphologymentioning
confidence: 99%
“…Finally, the blocks of chains are incorporated into a fibrillar structure [15]. This model holds for a number of different forms of polyethylene, including crystals (on which the model was originally proposed) and melt drawn films [18]. The present phenomenon (tendency of dislocating from spherulitic to fibrillar morphology as a result of microcellular process) may be explained using the Peterlin's model [16,17] as follows.…”
Section: Crystalline Morphologymentioning
confidence: 99%
“…High molecular symmetry and high cohesive energy between chains, require a fair degree of polymer crystallinity, which results in high tensile strength and high modulus of the fibers. Drummond et al 79 used atomic force microscopy (AFM) to study the structural changes due to external deformation. 76 Xiao et al 77 reported stress-enhancement of permeation rates in polyvinyl chloride geomembranes, but observed the opposite effect with highdensity polyethylene geomembranes (HDPE).…”
Section: Effect Of Mechanical Deformation On Permeationmentioning
confidence: 99%